2020
DOI: 10.1631/jzus.b2000043
|View full text |Cite
|
Sign up to set email alerts
|

Comparative transcriptomic analysis of vascular endothelial cells after hypoxia/re-oxygenation induction based on microarray technology

Abstract: Objective: To provide comprehensive data to understand mechanisms of vascular endothelial cell (VEC) response to hypoxia/re-oxygenation. Methods: Human umbilical vein endothelial cells (HUVECs) were employed to construct hypoxia/re-oxygenation-induced VEC transcriptome profiling. Cells incubated under 5% O 2 , 5% CO 2 , and 90% N 2 for 3 h followed by 95% air and 5% CO 2 for 1 h were used in the hypoxia/re-oxygenation group. Those incubated only under 95% air and 5% CO 2 were used in the normoxia control group… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(1 citation statement)
references
References 41 publications
0
1
0
Order By: Relevance
“…We found that the genes differentially expressed between mEC and bEC were not shared with those differentially expressed between OA grade 2 and grade 3 ECs. Furthermore, when we compared the transcriptomic profile of OA ECs with that of healthy HUVECs 23 , we did not find possible signatures induced by OA in both ECs as compared to a healthy endothelium. Taking these considerations together, we can suppose that the differential expression observed between OA bECs and mECs is mainly attributable to the different origin of endothelial cells, as widely reported in the literature for other healthy tissue types and organisms 2 , 4 .…”
Section: Discussionmentioning
confidence: 82%
“…We found that the genes differentially expressed between mEC and bEC were not shared with those differentially expressed between OA grade 2 and grade 3 ECs. Furthermore, when we compared the transcriptomic profile of OA ECs with that of healthy HUVECs 23 , we did not find possible signatures induced by OA in both ECs as compared to a healthy endothelium. Taking these considerations together, we can suppose that the differential expression observed between OA bECs and mECs is mainly attributable to the different origin of endothelial cells, as widely reported in the literature for other healthy tissue types and organisms 2 , 4 .…”
Section: Discussionmentioning
confidence: 82%